Exploring the Digital Landscape: Understanding and Adapting to Evolving Consumer Behavior in the Digital Age - Patel, Neerav; Chauhan, Rahul (Indonesian Journal Publisher, 2024)
This systematic review synthesizes findings from 24 scholarly papers sourced from Scopus and Emerald publications to provide insights into contemporary consumer behavior in the digital age. Key themes explored include the transformative impact of digitalization on consumer decision-making processes, the significance of privacy considerations, the importance of personalized marketing strategies, and the influence of external events such as the COVID-19 pandemic. Through an analysis of the literature, this review highlights the need for businesses to adapt their marketing strategies to meet the evolving expectations of empowered consumers in the digital landscape.